Sebaran Geografis Periwayat Shi>‘ah dan Nas}b - Aceng Abdul Kodir (Journal on Education, 2025)
This article tries to trace and explain the relation between the political movement and the hadith movement in the first three centuries of Islam, particularly in Shi’a and Nas}b sects. This research uses historical and geo-political approaches in analyzing the transmission of hadith conducted by these two sects. This articleshows that the transmitters of hadith who supported ‘Ali were mostly in Kufah, while those who hated Ali (Nas{b) were in Damascus.